(untitled) (Research, Society and Development, 2021)
Osteoarthritis is a commonly insidious, gradual, and slow musculoskeletal dysfunction characterized by wear of the articular cartilage and bone changes. Aquatic physiotherapy has great relevance in the treatment of patients with knee osteoarthritis, reducing pain and contributing to a significant improvement in quality of life. The aim of this study is to systematically review the effectiveness of aquatic physical therapy in reducing pain in patients and improving the quality of life in elderly patients with knee osteoarthritis. It is a systematic review of randomized clinical trials, analyzed by two independent reviewers, as recommended by the Prisma platform in the PubMed, PEDro and CENTRAL databases. Original studies using Aquatic Physical Therapy to reduce pain and improve quality of life in elderly patients with knee OA were included. The PEDro scale was used to analyze the methodological quality and analysis of risk of bias. Five studies were included. Aquatic Physiotherapy intervened to reduce pain and improve quality of life when compared to other intervention methods applied to elderly patients with knee OA. It is concluded that Aquatic Physical Therapy is an effective option for knee osteoarthritis, reducing pain levels and increasing the quality of life of the elderly.